Naphthalene Diimide Incorporated Thiophene-Free Copolymers with Acene and Heteroacene Units: Comparison of Geometric Features and Electron-Donating Strength of Co-units - Kim, Yiho; Hong, Jayeon; Oh, Joon Hak; Yang, Changduk (Chemistry of materials, 2013)
A family of naphthalene diimide (NDI)-based donor (D)-acceptor (A) copolymers with various acene- (benzene (Bz), naphthalene (Np), and pyrene (Py)) and heteroacene-type (selenophene (Se) and thiophene (Th)) donor rings has been designed and synthesized as a means to systematically understand structure–property relationships on the subject of the structural factor and electron-donating capability of the donor portions for applications in organic field-effect transistors (OFETs) based on NDIs. Alongside of two categories dealing with the lack or existence of the heteroatoms in the donor framework, the resulting copolymers can also be classified into ‘thiophene-free’ D–A copolymers (PNDI-Bz, PNDI-Np, PNDI-Py, and PNDI-Se) and thiophene-containing copolymer (PNDI-Th). The results from optical and electronic properties lead to the determination that the empirical electron-donating strength of donor co-units is in the order of Bz < Np < Py < Th < Se. In contrast with the similarity of the LUMO levels (−3.73∼−3.82 eV) due to the dominant NDI contribution to the polymer backbone, the HOMO levels are sensitive to the relative electron-donating ability and shown to primarily influence whether unipolar n-channel (PNDI-Bz and PNDI-Np) or ambipolar charge transport (PNDI-Py, PNDI-Se, and PNDI-Th) is observed in OFETs of the NDI-based copolymers. Intriguingly, regardless of the strong electron donors toward efficient intramolecular charge transfer (ICT), the best OFET performance is observed in the acene-based centrosymmetric copolymer PNDI-Np (5.63 × 10–2 cm2 V–1 s–1) when compared to those of the other copolymers with axisymmetric units. Thus, the present work highlights that the geometric features of the donors in NDI D–A copolymers strongly reflect the carrier mobility dynamics rather than inserting electron-rich donor moieties into the backbone to lower the band gap and further strengthen ICT.